2020
DOI: 10.31545/intagr/118413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage under unfavourable conditions on the caking properties and fungal contamination of potato starch and wheat flour

Abstract: In recent years, there has been growing interest in the elimination of undesirable phenomena in the processing of bulk materials. In this study, the relationship between the mechanical properties of caking, as analysed with FTIR structural measurements, and the phenomena connected with fungal growth were investigated in wheat flour and potato starch. The materials were stored in high humidity conditions at room temperature (20 ± 2 o C) in order to rapidly cause caking. The results showed changes in cake streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 29 publications
4
8
2
Order By: Relevance
“…This study showed that in sucrose samples caking can be initiated already in conditions with water activity above 0.75, but only above 0.8 does it become significant. A similar conclusion was drawn in our previous studies [ 22 ]. In high humidity higher strength values were observed in both wheat flour and potato starch.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This study showed that in sucrose samples caking can be initiated already in conditions with water activity above 0.75, but only above 0.8 does it become significant. A similar conclusion was drawn in our previous studies [ 22 ]. In high humidity higher strength values were observed in both wheat flour and potato starch.…”
Section: Resultssupporting
confidence: 93%
“…It may suggest that the development of microorganisms could also affect the density of the potato starch layer and, thus, increase the strength value. A similar effect was obtained in the work Wajs et al [ 22 ], where the amount of fungal contamination affected changes in the strength of the resulting agglomerates. The shortening of the first linear growth is, therefore, the result of the appearance of a dense layer, observed as the second peak.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations